2011
DOI: 10.3109/15622975.2011.620002
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal integrity and neurocognition in first-episode schizophrenia: A multidimensional study

Abstract: These results point to a relationship between verbal memory and hippocampal integrity in schizophrenia patients which might be independent from deficits in other memory domains. Disturbed verbal memory functions in FE-SZ might be linked specifically to hippocampal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 52 publications
3
18
0
3
Order By: Relevance
“…In our study, similar to these results, NAA levels in the hippocampus were significantly decreased in the CSPs when compared to healthy controls. Consistent with previous reports, this finding was not found in the FEP group, so it suggests a progressive process in schizophrenia (14)(15)(16)48).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, similar to these results, NAA levels in the hippocampus were significantly decreased in the CSPs when compared to healthy controls. Consistent with previous reports, this finding was not found in the FEP group, so it suggests a progressive process in schizophrenia (14)(15)(16)48).…”
Section: Discussionsupporting
confidence: 82%
“…Starting with Nasrallah et al 's study, a decreased hippocampal NAA level was supported by several other studies in schizophrenia patients, and it was reported that NAA decrease in the hippocampus was approximately 22% (52). Considering that the decrease in hippocampal NAA levels is a more consistent result when compared to those in other brain areas such as the frontal cortex, basal ganglion, thalamus, and cingulate cortex in CSPs, it may be interpreted as strong evidence for neuronal/axonal loss in the hippocampus in schizophrenia (14,16,20,(53)(54)(55). In our study, similar to these results, NAA levels in the hippocampus were significantly decreased in the CSPs when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Two studies found unaltered hippocampal Glx levels in medicated (Hasan et al . ) and unmedicated FEP (Wood et al . ) and in schizophrenia spectrum patients (Wood et al .…”
Section: H‐mrs Findings In Schizophreniamentioning
confidence: 99%
“…The hippocampus has well-studied roles in long-term and working memory, which are abilities that are often impaired in people with schizophrenia (Aleman et al, 1999;Libby et al, 2013). A reduction of hippocampal volume and/or alterations of hippocampal asymmetry have been found by independent studies and meta-analyses to associate with schizophrenia (Adriano et al, 2012;Gruber et al, 2008;Hasan et al, 2011;Haukvik et al, 2013;Jaaro-Peled et al, 2010;Shenton et al, 2010;Shepherd et al, 2012).…”
Section: Introductionmentioning
confidence: 99%